Nghiên cứu tổng hợp axit glycolic bằng phương pháp oxi hóa etylen glycol trên hệ xúc tác Au/Al2O3 và Au/C - Lâm và cộng sự, Hồ Sơn (Vietnam Journal of Chemistry, 2014)
The rate and the products of the oxidation of ethylene glycol on Au/C and Au/Al2O3 at room temperature have been studied. The oxidation of ethylene glycol carried out on Au/C gave  the conversion about 24%, and  selectivity of glycolic acid about 94%; on Au/Al2O3 gave the conversion  about 41% and  selectivity of glycolic acid about 60%. The products were analyzed by GCMS and the mechanism of these compounds formation was discussed.